Molecular cytogenetic evaluation of chromosomal microdeletions: the experience of a public hospital in Southern Brazil - Mariluce Riegel (Clinical and Biomedical Research, 2014)
Introduction: During the past few decades, the number of diseases identified to be caused by chromosomal microdeletions has increased quickly, bringing a new and crucial role for cytogenetics on the diagnosis of these conditions. The purpose of this study was to identify and characterize chromosomal microdeletions associated with malformation syndromes and intellectual disability.